Mechanisms of molecular differentiation of sex chromosomes in Lepidoptera and their evolution - Dalíková, Martina (Jihočeská univerzita, 2017)
Sex chromosomes represent a unique part of the genome in many eukaryotic organisms. They differ significantly from autosomes by their evolution, specific features, and meiotic behaviour. Recent advances in the knowledge of sex chromosomes in non-model organisms have been largely enabled by modern cytogenetic methods. The present study explores several topics related to sex chromosomes in Lepidoptera, the largest group of animals with female heterogamety, using methods of molecular cytogenetics, immunocytogenetics, and molecular biology. These topics include physical mapping of chromosomes by BAC-FISH, molecular differentiation and composition of the W chromosome, differences in the evolution of the W and Z chromosome, and meiotic sex chromosome inactivation. The results obtained brought new information not only about the W and Z chromosomes in Lepidoptera, but also about the evolution and specific features of sex chromosomes in general.
Mechanisms of molecular differentiation of sex chromosomes in Lepidoptera and their evolution
Keywords: sex chromosomes; evolution; Lepidoptera; satellite DNA; meiotic sex crhomosome inactivation; sex chromosomes; evolution; Lepidoptera; satellite DNA; meiotic sex crhomosome inactivation